The Moderation Effect of e-Trust and Big Data Quality in e-Grocery: An Empirical Research from Outside of Java Island. - et. al., Dendy Pramudito, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-grocery is the next big thing that change grocery retail landscape. Even in Indonesia still in the pilot phase towards success, e-grocers have started to retain e-loyalty of their customers. Although e-loyalty in e-grocery is important but it is less explored in e-commerce literature. Big data as part of industry 4.0 has been utilized in many retail include e-grocery and it plays important role to understand of consumer motivation and attract new customers. The purpose of this paper is to investigate the effect of e-trust and big data quality as moderating variable that help in building e-loyalty towards e-grocery business. An online survey was distributed to more than 130 respondents from many major cities outside of Java Island in Indonesia. Structural equation modeling was used and its results reflect the impact on e-loyalty. The main findings of this research are related with the importance of big data quality whether strengthen or not the relation between e-tailing quality and consumer motivation as antecedents of e-satisfaction that fostering e-loyalty in e-grocery business..